(untitled) (TEL Tempo, Espaço e Linguagem, 2021)
In this text we analyze the actions of Francisco Muniz Tavares, priest of the Regular Clergy of Pernambuco, in relation to the centralization policy of d. Pedro during the Independence of Brazil, highlighting the situation in the province of Pernambuco and how these actions were criticized by the Carmelite Friar Joaquim do Amor Divino, known as Friar Caneca, on the eve of the Confederation of the Equator in 1824.